Le Corbusier and the Immeuble-villas: The customer as a productive resource - Sequeira, M. (Inheritable resilience: Sharing values of global modernities - 16th International Docomomo Conference Tokyo Japan 2020+1 Proceedings, 2021)
In November 1922, at the Urbanism stand of the Autumn Salon of Paris, Le Corbusier presented for the first time the Immeuble-villas project. It emerged as a new housing typology with private spaces - 120 apartments - and communal spaces - warehouse, central kitchen, restaurant, laundromat, running track, solariums, as well as sports, gaming, study, and party halls. Each apartment consisted of a small home with a garden, inside a big collective housing building. In 1930, Le Corbusier published thirteen drawings related to this project together with a presentation text in Le Corbusier und Pierre Jeanneret: Ihr gesamtes Werk von 1910-1929, the first volume initially published in German of the Œuvre Complète. In it, he pointed out that the Immeuble-villas project was designed “in the back of a restaurant menu”. As usual, he relativized the creative process reducing it to an instant of inspiration. However, the amount of existing documents at the Foundation Le Corbusier about this project demonstrates that the conception process was far more complex. Apparently, the origin of the Immeuble-villas dates back to the contact Le Corbusier established with a prominent real estate society that was interested in realizing luxury buildings in Paris, where the French good taste was combined with the American sense of comfort: the Groupe de l'Habitation Franco-Américaine. While this relationship did not result in a concrete building, this potential client ended up playing a fundamental part in the project's genesis.